2003
DOI: 10.1097/00061198-200310000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Optic Disc Cup Progression in Treated Primary Open-Angle Glaucoma

Abstract: In treated patients with primary open-angle glaucoma, the rate of progressive optic disc cupping was slow (LCDR progression of 0.0068 per year). The higher yearly average intraocular pressure was significantly associated with a faster rate of cup progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…Correspondingly, Uchida et al [52] showed an association between increasing peripapillary atrophy and progressive glaucoma. In agreement with the latter studies, Kwon et al [53] observed an enlargement of peripapillary atrophy during a follow-up of at least 9 years in patients treated for primary open-angle glaucoma and progressive glaucomatous optic nerve damage. Ahn et al [54] investigated the correlation between a disc hemorrhage and peripapillary atrophy in glaucoma patients with a unilateral disc hemorrhage.…”
Section: Recent Studiessupporting
confidence: 71%
“…Correspondingly, Uchida et al [52] showed an association between increasing peripapillary atrophy and progressive glaucoma. In agreement with the latter studies, Kwon et al [53] observed an enlargement of peripapillary atrophy during a follow-up of at least 9 years in patients treated for primary open-angle glaucoma and progressive glaucomatous optic nerve damage. Ahn et al [54] investigated the correlation between a disc hemorrhage and peripapillary atrophy in glaucoma patients with a unilateral disc hemorrhage.…”
Section: Recent Studiessupporting
confidence: 71%
“…However, daily application, due to poor ocular bioavailability and other long-term side effects such as allergy and intolerance to medications, have negative effects on patient compliance, which leads to disease progression from suboptimal medical management of the disease resulting in poor IOP control. [2][3][4] Latanoprost, a lipophilic drug usually delivered in the form of an oil/water emulsion (Xalatan Liposomes, which have been shown to be biocompatible nanocarriers for ocular use, allows for delivery of both the lipophilic drug molecule as well as its hydrophilic active products, due to its physical structure of a polar core and lipophilic bilayer. 7 Liposomal encapsulation protects drug molecules from enzymatic hydrolysis in the physiological environment while in circulation, and thus increases stability.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported 0.76 (intraclass correlation) for LCDR. 1 Using CAP on stereo fundus photographs, Garway-Heath et al 5 reported interobserver CV of 8.1% and 17.1% for disc and neuroretinal rim area, respectively. Using digital monochromatic sequential stereo disc photographs (Discam), Shuttleworth et al 6 reported interobserver CV of 11.8%, 12.1%, and 17.9% for vertical, horizontal, and area CDR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Optic disc pallor was not used in determining the cup. 1 Next, (objective) DAP was performed on these same stereo images as described previously (Fig. 1).…”
Section: Patient Datamentioning
confidence: 99%
See 1 more Smart Citation